UPAYA GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MATA PELAJARAN QURAN HADITS KELAS XI DI MADRASAH ALIYAH NEGERI 2 TUREN KABUPATEN MALANG - Muhammad Fauzan Jailani; Abdul Jalil; Dian Muhammad Hakim (VICRATINA, 2021)
During the pandemic, educational institutions experienced obstacles in the teaching and learning process, this was also felt by MAn 2 Turen Malang where it was difficult for teachers to teach. However, this does not reduce the enthusiasm of the teacher in providing learning motivation to students. The purpose of this study was to determine the teacher's efforts in increasing the learning motivation of class XI students in the subject of Al-Qur'an Hadith at MAN 2 Turen Malang Regency. This research approach uses an approach approach, the type of approach is a case study, the data obtained in the form of observation, interviews, documentation. The data analysis technique is done by condensing the data, presenting the data and drawing conclusions. The informants used were the subjects of Al-Qur'an Hadith and several students of class XI MAN 2 Turen Malang. The results of the research carried out are learning planning in increasing the learning motivation of class XI students in the Al-Qur'an Hadith subject, teacher implementation in increasing student motivation in class XI at MAN 2 Turen, and teacher evaluation in increasing the motivation of class XI students in subjects Al-Qur'an Hadith at MAN 2 Turen. From the results found, namely during this pandemic, teachers continue to try to provide their best service in conveying material to students. The teacher also guides students to continue learning to read and write the holy verses of the Koran and hadith even in virtual conditions. In practice, the teacher succeeded in making students active in memorizing the holy verses of the Qur'an, understanding the contents of the Qur'an, and the teacher also always doing Tahsin al-Qur'an during offline lessons. The goal is that the teacher can see the makhorijul letters he reads. The teacher also evaluates in the form of an assessment rubik, with the aim that students pay attention to each value they have received.